PROSES PENANGANAN TELUR KERAPU TIKUS (Cromileptes Altivelis) DI BBRBLPP GONDOL - Muh. Sulaiman Dadiono; Indra Suryawinata (Jurnal Biogenerasi, 2022)
The purpose of this study was to determine the process of handling humpback grouper eggs (Cromileptes altivelis) at BBRBLPP Gondol Bali. The data collection method was carried out by means of observation, active participation and direct interviews. The process of handling humpback grouper eggs includes the process of handling initial eggs, egg selection, egg counting and egg observation. The initial handling of humpback grouper eggs begins with harvesting eggs which are carried out in the morning in an egg storage tank that has an egg collector installed. Egg selection is done to separate eggs of good quality and not good. Good quality eggs will float on the surface, are round, transparent and have a core. Quality eggs will not sink to the bottom and are milky white. The egg-calculation technique uses the manual method with the help of a petri dish and a 20 ml glass beaker. The results of the calculation of eggs obtained in one spawning of humpback grouper produced around 670,000 eggs for one broodstock pond of humpback grouper. Eggs using a 40x magnification microscope. The fertilized egg has a transverse line between the nucleus of the egg which is a developing embryo. The unfertilized egg does not have a transverse line which indicates the egg does not have an embryo.